Visualization of Architectural Design for the Arragement of the Wanasutan Tourism Park Area, Maguwoharjo - Prasetyo Febriarto; Hanantyo Sri Nugroho; Andri Zulfikar (SWAGATI : Journal of Community Service, 2026)
The problem at the community service location is regarding unused green land that needs to be processed and developed, according to requests from partners in Maguwoharjo Village, Depok District, Sleman Regency and local residents, who want the development and expansion of Wanasutan Park. The purpose of this community service program is to help process and expand the green land into a tourist attraction, with support in the form of architectural design visualization. The methods applied include the preparation and planning phase, development and design, with the results of the community service explaining the initial condition of the land in the form of an empty area and the condition after processing in the form of architectural design visualization in two dimensions and three dimensions. The conclusion of the community service activities shows that design through design visualization requires a collaborative approach involving various stakeholders starting from community representatives, the village government. Participatory and sustainable planning process through several meetings has proven important to produce a responsive design, and in accordance with shared needs.